Pengaruh Variasi Ekstrak Daun Kelor, Daun Sembukan, Daun Kapuk Terhadap Laju Korosi Baja ST 37 - Zuhairi, Rafi; Kosjoko; Nely Ana Mufarida (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Abstract : Corrosion is a common problem encountered in various sectors, particularly industrial and maritime applications that utilize ST 37 steel. The widespread use of synthetic chemical inhibitors is considered less environmentally friendly; therefore, alternative materials derived from natural sources are required. This study aims to analyze the effect of variations of three organic inhibitors—moringa leaf extract, sembukan leaf extract, and kapok leaf extract—on inhibiting the corrosion rate of ST 37 steel. The research method employed a laboratory experimental approach by immersing steel plates in each inhibitor for different durations of 1, 3, and 5 days, followed by immersion in seawater for 30 days. The corrosion rate was determined using the weight loss method, while inhibitor efficiency was evaluated by comparison with a control sample without inhibitor. The experimental results showed that moringa leaf extract exhibited the best performance with a 5-day inhibitor immersion, achieving the lowest corrosion rate of 0.09 mmpy and the highest efficiency of 89.8%, followed by kapok leaf extract with a corrosion rate of 0.16 mmpy and an efficiency of 81.38%. Sembukan leaf extract showed the highest corrosion rate among the inhibitors at 0.18 mmpy with an efficiency of 80.00%. These results indicate that longer inhibitor immersion periods enhance corrosion protection effectiveness. The findings highlight the potential of organic inhibitors as environmentally friendly alternatives for corrosion mitigation in industrial applications.